Pembrolizumab for the treatment of Progressive Multifocal Leukoencephalopathy (PML) in a patient with AIDS: A case report and literature review. (2022) - Chatterjee, Tulika; Roy, Moni; Lin, Rone-Chun; Almoujahed, Mohammad O.; Ahmad, Sharjeel
Abstract: Progressive multifocal leukoencephalopathy (PML) is an opportunistic central nervous system (CNS) infection caused by the reactivation of John Cunningham polyomavirus (JCV) from suppression of the host immune system due to conditions such as human immunodeficiency virus causing acquired immunodeficiency syndrome (HIV/AIDS), hematological malignancies, multiple sclerosis, and use of immunosuppressant medications. Pembrolizumab is an immune checkpoint inhibitor targeting programmed cell death protein-1 (PD-1) receptors on lymphocytes. In recent years its use is expanding to treat several malignancies and it is a drug of interest for the treatment of PML. In this case report, we present a case of an HIV/AIDS patient who was given a trial of pembrolizumab for treatment of PML. We also provide a literature review of the reported cases of use of this medication in other immunocompromised states.